2002
DOI: 10.1542/peds.110.2.e18
|View full text |Cite
|
Sign up to set email alerts
|

Underascertainment of Child Maltreatment Fatalities by Death Certificates, 1990–1998

Abstract: ABSTRACT. Objective. Child fatality review teams have emerged across the United States in the past decade to address the concern that systems of child protection, law enforcement, criminal justice, and medicine do not adequately assess the circumstances surrounding child fatality as a result of maltreatment.Methods. We compared data collected by a multidisciplinary child fatality review team with vital records for all children who were aged birth to 16 years and died in Colorado between January 1, 1990, and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(85 citation statements)
references
References 8 publications
(7 reference statements)
2
74
2
1
Order By: Relevance
“…50 Accurate estimates are difficult because of the difficulties in classification and in identifying the cause of death. [53][54][55][56] Patterns of violent death vary across the age spectrum, and do not form a homogeneous group (Box 2). [57][58][59] A study of 267 Serious Case Reviews into fatal cases of maltreatment in…”
Section: Fatal Maltreatment and Deaths From Assaultmentioning
confidence: 99%
“…50 Accurate estimates are difficult because of the difficulties in classification and in identifying the cause of death. [53][54][55][56] Patterns of violent death vary across the age spectrum, and do not form a homogeneous group (Box 2). [57][58][59] A study of 267 Serious Case Reviews into fatal cases of maltreatment in…”
Section: Fatal Maltreatment and Deaths From Assaultmentioning
confidence: 99%
“…Detailed review of child deaths in Missouri, North Carolina, Colorado, and, more recently, Michigan, California, and Rhode Island has revealed that approximately half of child abuse fatalities are unrecognized in vital statistics data. [3][4][5][6] The incidence of sudden infant death syndrome (SIDS) has decreased significantly since the 1992 AAP recommendations for safe sleeping positions for infants. 7,8 Evaluation of more recent declines in SIDS rates in the United States suggest that, despite the significant decreases in SIDS deaths over the past 15 years, more recent declines might be attributable to an increase in diagnostic coding of asphyxia, suffocation, and other causes of sudden, unexpected infant death.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compared with vital records, child-fatality-review programs often document detailed information about the cause and circumstances of death and record information on a wider variety of risk factors. 5,7,11 We published a case-control study 2 in Pediatrics in 2002 using the first 3 years of Missouri Child Fatality Review Program (CFRP) data (1992)(1993)(1994). We reported that children residing in households with adults unrelated to them were 8 times as likely to die of maltreatment than children residing with only 2 biological parents and showed no increased risk of maltreatment death to children in households with a single parent and no other adult residents.…”
mentioning
confidence: 99%